2010
DOI: 10.3346/jkms.2010.25.6.980
|View full text |Cite
|
Sign up to set email alerts
|

Skin Aging and Photoaging Alter Fatty Acids Composition, Including 11,14,17-eicosatrienoic Acid, in the Epidermis of Human Skin

Abstract: We investigated the alterations of major fatty acid components in epidermis by natural aging and photoaging processes, and by acute ultraviolet (UV) irradiation in human skin. Interestingly, we found that 11,14,17-eicosatrienoic acid (ETA), which is one of the omega-3 polyunsaturated acids, was significantly increased in photoaged human epidermis in vivo and also in the acutely UV-irradiated human skin in vivo, while it was significantly decreased in intrinsically aged human epidermis. The increased ETA conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 13 publications
2
56
1
Order By: Relevance
“…Kim et al [32] reported that the composition of FAs is changed in aged skin and the synthesis of FAs is decreased in UV-irradiated skin [33], which are opposite outcomes compared to ours, suggesting that there may be specific pathways for glycation-induced upregulation of the FA metabolism.…”
Section: Discussioncontrasting
confidence: 51%
“…Kim et al [32] reported that the composition of FAs is changed in aged skin and the synthesis of FAs is decreased in UV-irradiated skin [33], which are opposite outcomes compared to ours, suggesting that there may be specific pathways for glycation-induced upregulation of the FA metabolism.…”
Section: Discussioncontrasting
confidence: 51%
“…Moreover, aged epidermis exhibits a decreased rate of transepidermal water loss, abnormal cytokine/growth factor signaling and a reduction in epidermal lipid synthesis [18,32]. Interestingly, the omega-3 polyunsaturated fatty acid 11,14,17-eicosatrienoic acid was found to be increased in photoaged human epidermis and also after UV irradiation, whereas a decrease was found in intrinsically aged human epidermis [33]. A deficiency of IL-1 signaling in murine aged epidermis, which may contribute to epidermal barrier abnormality, has been reported by Ye et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…Its structure is maintained by several enzymes; matrix metalloproteinases (MMPs) secreted by fibroblasts degrade collagen, while MMP activity is inhibited by tissue inhibitor of tissue inhibitor of metalloproteinases (TIMPs). During the aging process, MMP expression gradually increases and TIMP expression decreases, promoting collagen degradation and reducing skin elasticity (7,8). …”
Section: Introductionmentioning
confidence: 99%